1991
DOI: 10.1002/hed.2880130303
|View full text |Cite
|
Sign up to set email alerts
|

Incisional or excisional neck‐node biopsy before definitive radiotherapy, alone or followed by neck dissection

Abstract: An analysis of 508 patients (660 heminecks) with head and neck squamous cell carcinoma and clinically positive neck nodes who were treated with radiotherapy alone to the primary lesion (with or without a neck dissection) was conducted to determine if open neck-node biopsy before definitive treatment adversely affected the probability of control of neck disease, the risk of distant metastasis, or the cause-specific survival rate. The prognostic factors analyzed included biopsy status of the neck, N stage, neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 13 publications
1
26
0
2
Order By: Relevance
“…Therefore, if sufficient evidence is noted on the excisional biopsy specimen to warrant radiotherapy (ie, multiple nodes or extracapsular extension), we do not ask the surgeons to perform a radical neck dissection, because we believe radiotherapy after excisional biopsy can result in comparable local control as long as the gross tumor has been excised and only microscopic disease remains. Other investigators have reported similar experience, 19,20 although contradictory data also exist. 13,15 We do not consider excisional biopsy alone an appropriate initial oncologic therapy, because the literature does not support this approach.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, if sufficient evidence is noted on the excisional biopsy specimen to warrant radiotherapy (ie, multiple nodes or extracapsular extension), we do not ask the surgeons to perform a radical neck dissection, because we believe radiotherapy after excisional biopsy can result in comparable local control as long as the gross tumor has been excised and only microscopic disease remains. Other investigators have reported similar experience, 19,20 although contradictory data also exist. 13,15 We do not consider excisional biopsy alone an appropriate initial oncologic therapy, because the literature does not support this approach.…”
Section: Discussionmentioning
confidence: 78%
“…195,196 The high rate of morbidity of the procedure 197,198 and the hindrance of subsequent therapy because of scarring or vascular impairment [197][198][199] are other reasons for caution. Not all authors agree, however, on the detrimental effect of pretreatment biopsy.…”
Section: Miscellaneous Lesionsmentioning
confidence: 97%
“…In several studies, the investigators found no differences in the recurrence of neck disease or survival time between patients who underwent pretreatment open biopsy and patients who had biopsies at the time of definitive treatment, but the results concerning rates of distant metastases are contradictory. [196][197][198] Finally, the physician must remember that the application of proper oncologic, radiotherapeutic, and surgical techniques is probably more important than the effect of a pretreatment biopsy. 189,[196][197][198][199] Ancillary studies include chest, paranasal, and upper gastrointestinal radiographs, the last with oral barium; mammography; and radioisotope scans of the thyroid gland.…”
Section: Miscellaneous Lesionsmentioning
confidence: 99%
“…36 On the basis of the data reviewed previously, the probability of long-term survival seems to be similar after either treatment option.…”
mentioning
confidence: 91%